Jihad dan Pentadbiran Tentera Menurut Perspektif Ulama Bosnia-Herzegovina Zaman Pertengahan: Jihad and Military Administration from the Perspective of Bosnian-Herzegovinian Scholars in the Medieval Era - Hamzah, Amer Hudhaifah (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2020)
Jihad is one of the most active activities carried out by the Ottoman Turkish government as a means to propagate Islamic teachings, especially in Christian regions in Europe. The conquest policy based on verse 6 of Surah al-Tawbah is evident in their will and poetry. However, this vision was often blurred in the eyes of the successors of the Ottoman sultans due to the worldly pleasures they enjoyed after the conquest of Constantinople in 1453. This caught the attention of a medieval Bosnian scholar named Hasan Kâfî el-Akhisârî, who wrote a critical work addressing the shortcomings of the Ottoman leaders. In the manuscript titled "Usul al-Hikam fi Nizam al-cAlam," Shaykh Hasan Kâfî advised the Ottoman government and military leaders on the deficiencies, especially during their Jihad operations in Europe. In general, Jihad and the administration of the military, according to Shaykh Hasan Kâfî, were built on the foundations of the Holy Quran, Sunnah, and the wisdom of past scholars. For him, Jihad aimed to establish universal justice. Through this system, a sultan was given divine authority as Nizam al-cAlam. However, deficiencies in the administration of the Ottoman military that occurred in 1595 demonstrated shortcomings in the Ottoman Sultan’s administration at the time. Mistakes that had been made since the reign of Sultan Murad III in 1580 emphasized the importance of implementing Islamic justice while entrusting tasks to qualified individuals. The role of the vizier was also crucial in ensuring the integrity of the institution. The Sultan should consider the advice of the consultative assembly and advisors (scholars) before making significant decisions of public interest. The people should be treated justly, with kindness and compassion since they hold the majority of power. The Sultan should also respect the comrades of his father and not rush to favor younger individuals in tasks to prevent any ill feelings. Regarding military preparations, Shaykh Hasan Kâfî emphasized the importance of regularly monitoring the readiness of the military, including both the number and quality of weapons. The development of enemy weaponry technology should be continuously monitored to prevent the Islamic military from falling behind in using modern weapons. If a Sultan enters the battlefield, he should not leave his standard, and provisions should be made to confuse the enemy. Military leaders should constantly foster qualities of patience, steadfastness, and bravery in their troops, always advising and reminding each other. Shaykh Hasan Kâfî pointed the importance of faith as a factor in the success of any operation because he saw victory (الظفر) closely related to the help (العون) from Allah. Therefore, he made the core of success the goodness (الصلاح) and piety (التقوى), while disobedience (العصيان) and transgression (البغي) were seen as factors of failure. He also stated that a truce is good, and fighting those who seek protection is the greatest mistake a military leader can make. Among the criticisms made by Shaykh Hasan Kafi against the Ottoman leadership were the appointment of unqualified individuals during Sultan Murad III’s administration, which resulted in the replacement of the Grand Vizier 12 times in 12 years (1574-1595). A group of Janissaries boldly defied Sultan Murad III’s order in 1574 that prohibited alcohol, leading him to eventually relax the ban to a non-intoxicating extent. Some Janissaries also deserted the battlefield during minor incursions, raiding Muslim settlements in the Bosnian Eyalet, looting, disturbing women and children, and forcing civilians to replace them in battle. This tragedy continued for several years since the German (Duchy of Styria) forces began launching attacks along the border of the Bosnian Eyalet in 1592. While it is fair to criticize the Ottoman government for the shortcomings that occurred, this does not mean that the movement had deviated from the path of Islam, and negative Orientalist claims about the forced conversion of European Christians to Islam by the Ottoman military are not accurate.